MR spectroscopy in opiate maintenance therapy: association of glutamate with the number of previous withdrawals in the anterior cingulate cortex - Hermann, Derik; Vollstädt-Klein, Sabine; Kiefer, Falk; Mann, Karl; Ende, Gabriele (Addiction biology, 2012)
Pre-clinical research indicates that opioids reduce extracellular glutamate in acute opioid treatment, whereas during withdrawal, glutamatergic neurotransmission is increased and withdrawal symptoms can be blocked by glutamate receptor antagonists. The glutamate hypothesis of addiction suggests that withdrawal-associated hyperglutamatergic states destabilize the glutamatergic system chronically and contribute to relapse. magnetic resonance spectroscopy at three tesla optimized for glutamate assessment (TE 80 ms) was performed in the anterior cingulate gyrus (ACC) and frontal white matter (fWM) of 17 opiate-dependent patients during opiate maintenance therapy and 20 healthy controls. Controlling for age and gray matter content, glutamate in the ACC was positively associated with the number of previous withdrawals. For glutamate + glutamine (Glx), a significant group-age interaction was found. Whereas Glx declines with age in healthy controls, Glx increases with age in opiate-dependent patients. The number of previous withdrawals did not correlate with age. In fWM spectra, increased Cho concentrations were observed in opiate-dependent patients. Both new findings, the positive correlation of glutamate and previous withdrawals and increasing Glx with age in contrast to an age-dependent Glx decrease in controls indicate a destabilization of the glutamate system in opiate-dependent patients and support the glutamate hypothesis of addiction. Increased Cho concentrations in fWM corroborate findings of WM abnormalities in opioid-dependent subjects.